CAAP48, a New Sepsis Biomarker, Induces Hepatic Dysfunction in an in vitro Liver-on-Chip Model - Blaurock-Möller, Nancy; Gröger, Marko; Siwczak, Fatina; Dinger, Julia; Schmerler, Diana; Mosig, Alexander S.; Kiehntopf, Michael (Frontiers in Immunology, 2019)
Sepsis is a leading cause of mortality in the critically ill, characterized by life-threatening organ dysfunctions due to dysregulation of the host response to infection. Using mass spectrometry, we identified a C-terminal fragment of alpha-1-antitrypsin, designated CAAP48, as a new sepsis biomarker that actively participates in the pathophysiology of sepsis. It is well known that liver-dysfunction is an early event in sepsis-associated multi-organ failure, thus we analyzed the pathophysiological function of CAAP48 in a microfluidic-supported in vitro liver-on-chip model. Hepatocytes were stimulated with synthetic CAAP48 and several control peptides. CAAP48-treatment resulted in an accumulation of the hepatocyte-specific intracellular enzymes aspartate- and alanine-transaminase and impaired the activity of the hepatic multidrug resistant-associated protein 2 and cytochrome P450 3A4. Moreover, CAAP48 reduced hepatic expression of the multidrug resistant-associated protein 2 and disrupted the endothelial structural integrity as demonstrated by reduced expression of VE-cadherin, F-Actin and alteration of the tight junction protein zonula occludens-1, which resulted in a loss of the endothelial barrier function. Furthermore, CAAP48 induced the release of adhesion molecules and pro- and anti-inflammatory cytokines. Our results show that CAAP48 triggers inflammation-related endothelial barrier disruption as well as hepatocellular dysfunction in a liver-on-chip model emulating the pathophysiological conditions of inflammation. Besides its function as new sepsis biomarker, CAAP48 thus might play an important role in the development of liver dysfunction as a consequence of the dysregulated host immune-inflammatory response in sepsis.